The Bibliographical Activities of the Kharkiv Public Library - Мамон, Вячеслав Євгенович (ХДАК, 2025)
The Kharkiv Public Library, established in 1886, emerged as a significant cultural and educational center in the region. Its contribution to the development of library science, particularly through the systematization and cataloging of literature, marked a new chapter in bibliographic practices. One of the library’s earliest achievements was the publication of the First Catalog of the Kharkiv Public Library in the latter half of 1886. This catalog, containing 1,410 book titles systematically arranged into sections such as fiction, science and applied knowledge, children’s books, folk literature, and periodicals, became a valuable resource for readers. It was distributed in 600 copies, making it widely accessible. The library’s bibliographic efforts advanced further in 1887 with the release of a systematic catalog spanning 319 pages and encompassing over 5,000 book titles. This catalog included an alphabetical index, significantly enhancing its usability and functionality for researchers and general readers alike.
Keywords: Харківська громадська бібліотека; історія бібліотек Харкова; Харківська державна наукова бібліотека імені В. Г. Короленка